2022
DOI: 10.1136/bmjgh-2021-007643
|View full text |Cite
|
Sign up to set email alerts
|

TB morbidity estimates overlook the contribution of post-TB disability: evidence from urban Malawi

Abstract: IntroductionDespite growing evidence of the long-term impact of tuberculosis (TB) on quality of life, Global Burden of Disease (GBD) estimates of TB-related disability-adjusted life years (DALYs) do not include post-TB morbidity, and evaluations of TB interventions typically assume treated patients return to pre-TB health. Using primary data, we estimate years of life lost due to disability (YLDs), years of life lost due to premature mortality (YLL) and DALYs associated with post-TB cardiorespiratory morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…This is clearly of relevance to the majority global HIV population who bear the additional burden of endemic TB. The findings reflect recent work from Malawi describing how long-term negative sequelae of pulmonary TB both on airways obstruction [reduced forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC)] and bronchiectasis, and their corresponding symptoms, are common at the end of TB treatment and although reducing over time, persist indefinitely in a significant minority, particularly those also living with HIV [14,15].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…This is clearly of relevance to the majority global HIV population who bear the additional burden of endemic TB. The findings reflect recent work from Malawi describing how long-term negative sequelae of pulmonary TB both on airways obstruction [reduced forced expiratory volume in 1 s (FEV1) and forced vital capacity (FVC)] and bronchiectasis, and their corresponding symptoms, are common at the end of TB treatment and although reducing over time, persist indefinitely in a significant minority, particularly those also living with HIV [14,15].…”
supporting
confidence: 83%
“…A question which the authors did not directly investigate, is the effect on health-related quality of life (HQoL) from CLD in their population. OLD has been associated with lower HQoL elsewhere in PWH [18], as has OLD secondary to TB [15] and may be predicted to progress with age [19]. This will be important to quantify using universal/generalizable measures such as the EQ-5D-5L both to understand the impact of CLD relative to Here the authors correctly highlight the greater importance of addressing TB risk over smoking cessation, arguably the priority intervention in HICs.…”
mentioning
confidence: 99%
“…In addition to respiratory symptoms, there was an increased morbidity and mortality of cardiovascular disease in post-patients with TB [ 54 ]. These studies suggested that, among those who have been cure of TB, except for COPD, other respiratory diseases, cardiovascular diseases, and neurological damage were also related to the disease burden of post-TB [ 55 ]. Therefore, when other systemic diseases caused by post-TB were considered, the burden of post-TB in Inner Mongolia might be significantly heavier than our results.…”
Section: Discussionmentioning
confidence: 99%
“… 64 Recent evidence from Blantyre, Malawi, demonstrated that over 90% of projected lifetime YLD was concentrated within the most severely affected 20% of survivors. 65 Per-case post-TB burden estimates are greater among women, younger people, HIV-positive individuals and those from countries with high-incidence rates. 65 , 72 A model of some of the psychological and socioeconomic consequences that contribute to poor HRQoL, examples of tools used to measure these and how PTLD contributes to the burden of TB disease is shown in Figure 4 .…”
Section: Post-tb Economic Social and Psychological Wellbeingmentioning
confidence: 99%